Fostering Communities of Learning in Two Portuguese Pre-School Classrooms Applying the Movimento da Escola Moderna (MEM) Pedagogy - Folque, Maria Assunção (2011)
This paper reports upon a Portuguese pedagogical model, where children engage with the teacher in planning and assessment during routine activities like “Council Meetings”, “Communication Time”, and using specific tools such as an “Activities Chart” and a “Diary”. The paper questions how these processes generate a community of practice in ´learning to learn´ with children aged 3 to 6. The study developed a theoretical framework using socio-cultural theory where action is mediated through the use of artefacts/tools and the communities’ social structures: roles, rules, division of labour and access to resources (Lave and Wenger 1991). This literature was complemented by a study of the children’s “learning to learn” which provided a focus on specific learning objects (meta-learning and learning dispositions such as learning orientation). Two pre-school classrooms were studied over one year using observations, video recordings, interviews with teachers and children, and analysis of two piloting tools: the “Diary” and the “Activity Chart”. Both classrooms provided “communities of learning” where children were encouraged to self-regulate their learning and engage in collaborative activities, transforming their leading activity from playing with others to learning with others (Siraj-Blatchford 2007). Despite these general results, each classroom produced a distinctive learning culture rooted in the individual teachers’ knowledge and control of the classroom community and interactions.